EKSISTENSI PEMELUK AGAMA YAHUDI DI MANADO - Zaenal Abidin (Harmoni, 2015)
This study is conducted to figure out the existence of Jews in Manado. The study concerns on the government services to all adherents not only major or minor religion, including Jewish. Existence aspects investigated are brief history, main teaching, and adherent spread. This qualitative study uses post-colonial perspective theory. Gayatri C Spivak found subaltern theory and revealed that Jews came to Indonesia from Netherland from 1800 until 1930. They are ancestry of Dutch, Polish, Portuguese, German, and Belgian (employee and army) and Iraq (merchant and enterpreneur). Theologically, Jews believe on God, Moses as prophet and Messiah will come to the Earth. Three scriptures used by Jews are Taurat, Talmut, and Tanach. Jews who are in Manado, Indonesia are classified into two, Orthodox Jews and Reform Jews.